Análisis fílmico de la película ecuatoriana En el nombre de la hija , para un ejercicio de crítica cinematográfica - Velarde Coba, Andrés (2015)
This investigation is an analysis about the Ecuadorian movie called “En el nombre de la hija”, in order to do a cinematographic critic that be able to establish a dialogue direct and indirect about it. In the first part of this paper there are categories and concepts that connect the cinema with the communication and the ideology from totality perspective, through a bibliographic study those arguments in a theory way the content. Besides this paper has a lecture about the filmic text through a methodology, that lent to understand not only the text but the context and the use of narratives resources. All this information is going to be like a synthesis in a critic essay that tries to get reflexions about the representations in the film and the context about it as social and ideological constructions. This academic activity try to help to the development of theories investigation, since the communication like a scientific social exercise in order to improve somehow with the cinematographic national industry and their representations.